Diffuse interstitial fibrosis assessed by cardiac magnetic resonance is associated with dispersion of ventricular repolarization in patients with hypertrophic cardiomyopathy. Issue 3 (19th November 2016) - Hurtado‐de‐Mendoza, David; Corona‐Villalobos, Celia P.; Pozios, Iraklis; Gonzales, Jorge; Soleimanifard, Yalda; Sivalokanathan, Sanjay; Montoya‐Cerrillo, Diego; Vakrou, Styliani; Kamel, Ihab; Mormontoy‐Laurel, Wilfredo; Dolores‐Cerna, Ketty; Suarez, Jacsel; et al.
Abstract: Background: Hypertrophic cardiomyopathy (HCM) is characterized by myocyte hypertrophy, disarray, fibrosis, and increased risk for ventricular arrhythmias. Increased QT dispersion has been reported in patients with HCM, but the underlying mechanisms have not been completely elucidated. In this study, we examined the relationship between diffuse interstitial fibrosis, replacement fibrosis, QTc dispersion and ventricular arrhythmias in patients with HCM. We hypothesized that fibrosis would slow impulse propagation and increase dispersion of ventricular repolarization, resulting in increased QTc dispersion on surface electrocardiogram (ECG) and ventricular arrhythmias. Methods: ECG and cardiac magnetic resonance (CMR) image analyses were performed retrospectively in 112 patients with a clinical diagnosis of HCM. Replacement fibrosis was assessed by measuring late gadolinium (Gd) enhancement (LGE), using a semi‐automated threshold technique. Diffuse interstitial fibrosis was assessed by measuring T1 relaxation times after Gd administration, using the Look–Locker sequence. QTc dispersion was measured digitally in the septal/anterior (V1–V4), inferior (II, III, and aVF), and lateral (I, aVL, V5, and V6) lead groups on surface ECG. Results: All patients had evidence of asymmetric septal hypertrophy. LGE was evident in 70 (63%) patients; the median T1 relaxation time was 411±38 ms. An inverse correlation was observed between T1 relaxation time and QTc dispersion in leads V1–V4 ( p <0.001). Patients with HCM who developed sustained ventricular tachycardia had slightly higher probability of increased QTc dispersion in leads V1–V4 (odds ratio, 1.011 [1.004–1.0178, p =0.003). We found no correlation between presence and percentage of LGE and QTc dispersion. Conclusion: Diffuse interstitial fibrosis is associated with increased dispersion of ventricular repolarization in leads, reflecting electrical activity in the hypertrophied septum. Interstitial fibrosis combined with ion channel/gap junction remodeling in the septum could lead to inhomogeneity of ventricular refractoriness, resulting in increased QTc dispersion in leads V1–V4.